World of Difference A Moral Perspective on Social Inequality - Ellemers, Naomi (Amsterdam University Press, 2017)
Public debates tend to see social inequality as resulting from individual decisions people make, for instance with respect to their education or lifestyle. Solutions are often sought in supporting individuals to make better choices. This neglects the importance of social groups and communities in determining individual outcomes. A moral perspective on social inequality questions the fairness of insisting on individual responsibilities, when members of some groups systematically receive fewer opportunities than others. The essays in this book have been prepared by experts from different disciplines, ranging from philosophy to engineering, and from economics to epidemiology. On the basis of recent scientific insights, World of Difference examines how group memberships impact on individual outcomes in four key domains: health, education and work, migration, and the environment. This offers a new moral perspective on social inequality, which policy makers tend to neglect.